A Bibliometric Analysis (2015-2025): Research on the Implementation of Problem-Based Learning Using Visual Media in Physics Education - Katarina Sanca; Dwikoranto; Rahmatta Thoriq Lintangesukmanjaya; Indri Hapsari Khansa; Sukarni; Marsini (Universitas Muhammadiyah Makassar, 2026)
The rapid growth of digital technology has encouraged physics education to adopt more student-centered and visually supported learning approaches, particularly because many physics concepts are abstract, mathematically complex, and difficult for students to understand through conventional instruction. Problem-Based Learning (PBL) supported by visual media has been widely recognized as a promising approach for improving conceptual understanding, problem-solving skills, and student engagement; however, the development of this research area has not been comprehensively mapped. This study aims to analyze research trends on the implementation of PBL using visual media in physics education during the 2015-2025 period. A bibliometric method was employed using Scopus-indexed publications as the data source. A total of 137 selected documents were exported as CSV files and analyzed using VOSviewer to examine publication trends, country contributions, document types, relevant authors, keyword co-occurrence networks, thematic clusters, overlay visualizations, and highly cited documents. The findings show a consistent increase in publications, with the United States, China, and Indonesia emerging as the most productive contributing countries. The keyword analysis identified eight major research clusters, indicating that studies in this field are strongly associated with physics education, students, simulations, augmented reality, virtual reality, artificial intelligence, image processing, and learning outcomes. The overlay visualization revealed a thematic shift from conventional visual media toward more interactive, immersive, and computational technologies. The novelty of this study lies in its integrated bibliometric mapping of PBL, visual media, and physics education over the last decade. This study concludes that visual media play an important role in strengthening PBL-based physics learning and provides evidence-based directions for future research and instructional innovation in physics education.